Association of the VEGFR2 gene His472Gln polymorphism with endurance-related phenotypes - Ahmetov, I.; Hakimullina, A. M.; Popov, D. V.; Lyubaeva, E. V.; Missina, S. S. (European Journal of Applied Physiology, 2009)
Vascular endothelial growth factor receptor 2 (VEGFR2) is essential to induce the full spectrum of VEGF angiogenic responses to aerobic training. In the present study, we examined the impact of the functional His472Gln polymorphism of the VEGFR2 gene on elite athlete status, endurance performance and muscle fibre type composition. Four hundred and seventy-one Russian athletes were prospectively stratified into four groups according to event duration, distance and type of activity, covering a spectrum from the more endurance-oriented to the more power-oriented. VEGFR2 genotype and allele frequencies were compared to 603 controls. To examine the association between VEGFR2 genotype and fibre type composition, vastus lateralis muscle biopsies were obtained from 45 physically active healthy men and 23 all-round speed skaters. In addition, 76 competitive rowers performed incremental endurance exercise to allow analysis of genotype associations with exercise responses. We found that the frequency of the VEGFR2 472Gln allele was significantly higher in endurance-oriented athletes compared to controls (36.8 vs. 27.4%, P = 0.0006). Relative VO2max was significantly greater in the VEGFR2 472Gln allele carriers compared with the His/His homozygotes of the sub-elite female rower group only. Genotype-specific differences were found for the proportion of slow-twitch fibres in both athletes and controls, which was ~10.1 and ~7.4% higher in the His/Gln and Gln/Gln genotypes than in the His/His genotype group, respectively. In conclusion, we have shown for the first time that variation in the VEGFR2 gene is associated with elite athlete status, endurance performance of female rowers and muscle fibre type composition.